Diagnostic and Prognostic Significance of Complement in Patients With Alcohol‐Associated Hepatitis. Issue 3 (22nd November 2020) - Fan, Xiude; McCullough, Rebecca L.; Huang, Emily; Bellar, Annette; Kim, Adam; Poulsen, Kyle L.; McClain, Craig J.; Mitchell, Mack; McCullough, Arthur J.; Radaeva, Svetlana; Barton, Bruce; Szabo, Gyongyi; et al.
Abstract : Background and Aims: Given the lack of effective therapies and high mortality in acute alcohol‐associated hepatitis (AH), it is important to develop rationally designed biomarkers for effective disease management. Complement, a critical component of the innate immune system, contributes to uncontrolled inflammatory responses leading to liver injury, but is also involved in hepatic regeneration. Here, we investigated whether a panel of complement proteins and activation products would provide useful biomarkers for severity of AH and aid in predicting 90‐day mortality. Approach and Results: Plasma samples collected at time of diagnosis from 254 patients with moderate and severe AH recruited from four medical centers and 31 healthy persons were used to quantify complement proteins by enzyme‐linked immunosorbent assay and Luminex arrays. Components of the classical and lectin pathways, including complement factors C2, C4b, and C4d, as well as complement factor I (CFI) and C5, were reduced in AH patients compared to healthy persons. In contrast, components of the alternative pathway, including complement factor Ba (CFBa) and factor D (CFD), were increased. Markers of complement activation were also differentially evident, with C5a increased and the soluble terminal complement complex (sC5b9) decreased in AH. Mannose‐binding lectin, C4b, CFI, C5, and sC5b9 were negatively correlated with Model for End‐Stage Liver Disease score, whereas CFBa and CFD were positively associated with disease severity. Lower CFI and sC5b9 were associated with increased 90‐day mortality in AH. Conclusions: Taken together, these data indicate that AH is associated with a profound disruption of complement. Inclusion of complement, especially CFI and sC5b9, along with other laboratory indicators, could improve diagnostic and prognostic indications of disease severity and risk of mortality for AH patients.